HISTORY OF INTERNET JOURNALISM IN KARAKALPAKSTAN - Bazarbaeva Anar G’ayratdin qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article says that with the advent of the Internet in Karakalpakstan, the Internet has become closer in the media, as well as the emergence of Internet journalism in Karakalpakstan.Digital journalism, also known as online journalism, is a contemporary form of journalism where editorial content is distributed via the Internet, as opposed to publishing via print or broadcast. What constitutes digital journalism is debated by scholars; however, the primary product of journalism, which is news and features on current affairs, is presented solely or in combination as text, audio, video, or some interactive forms like newsgames, and disseminated through digital media technology.The first type of digital journalism, called teletext, was invented in the UK in 1970. Teletext is a system allowing viewers to choose which stories they wish to read and see it immediately. The information provided through teletext is brief and instant, similar to the information seen in digital journalism today.[citation needed] The information was broadcast between the frames of a television signal in what was called the Vertical Blanking Interval or VB.American journalist, Hunter S. Thompson relied on early digital communication technology beginning by using a fax machine to report from the 1971 US presidential campaign trail as documented in his book Fear and Loathing on the Campaign Trail.